2008
DOI: 10.1002/pros.20753
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐Surface labeling and internalization by a fluorescent inhibitor of prostate‐specific membrane antigen

Abstract: Our results suggest that potent, small-molecule inhibitors of PSMA can be utilized as carriers for targeted delivery for prostate cancer for future imaging and therapeutic applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
103
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(120 citation statements)
references
References 51 publications
17
103
0
Order By: Relevance
“…This additional acid group did not negatively impact the affinity for PSMA. All 4 compounds exhibited high affinity and specificity for PSMA and internalized on binding to PSMA in LNCaP cells, as did previously described small molecules (14,40) and antibodies (10).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This additional acid group did not negatively impact the affinity for PSMA. All 4 compounds exhibited high affinity and specificity for PSMA and internalized on binding to PSMA in LNCaP cells, as did previously described small molecules (14,40) and antibodies (10).…”
Section: Discussionsupporting
confidence: 77%
“…However, given the widespread availability of 99m Tc and the presence of SPECT cameras in most hospitals throughout the world, the development of a 99m Tc-labeled agent targeting a cell surface protein that is upregulated in prostate cancer may be advantageous. To improve prostate cancer detection for staging disease and to better monitor therapy and disease recurrence, we and others have attempted to image prostate cancer by targeting PSMA using small molecules (13)(14)(15)(18)(19)(20)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49) and antibodies that target the extracellular domain (41). Our previous work focused on using the glutamate-urea-lysine pharmacophore radiolabeled with an isotope of iodine that exhibited high affinity for PSMA and was found to localize to prostate cancer in animal models and in clinical trials (13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies revealed that PSA inhibits the growth and migration of endothelial cells by inhibiting endothelial cell response to the fibroblast growth factor 2 (FGF-2) and vascular endothelial growth factor (VEGF). They have the ability cleave plasminogen, causing the release of biologically active angiostatin-like fragments and can essentially slow the progression of the disease through this antiangiogenic activity [32,60]; in addition to that, it has been revealed that PSA-inhibitors suppress the antiangiogenic effect of PSA in an angiogenesis model [61].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the successful deployment of PSMA inhibitors as targeting motifs for imaging and therapeutic agents suggests that such constructs can serve as pharmacokinetic alternatives to antibodies (25)(26)(27)(28)(29)(30). These studies also support the concept that such compounds may also be applied as diagnostic and therapeutic agents targeted to PSMA-positive (PSMA+) tumor-associated vasculatures of various non-prostatic tumors.…”
Section: Introductionmentioning
confidence: 99%